Picking Winners and Losers: A Structural Examination of Tax Subsidies to the Energy Industry - Roberts, Tracey M. (Columbia Journal of Environmental Law, 2019)
In debates over whether government should continue to subsidize renewable energy, politicians have repeatedly warned that government should not be “picking winners and losers.” This way of framing the debate undermines sensible policy analysis in two ways. First, it obscures the long history of federal support for fossil fuels; the United States has been picking winners and losers for over 100 years. Second, it fails to articulate what it means to “pick winners and losers,” to explain why doing so is less efficient than pursuing other economic policies, and to inquire why this suboptimal choice has been made. This article addresses these failings by examining two sets of tax subsidies to the energy industry, one for fossil fuels and the other for renewables. Part II of this article describes economic situations that would justify government intervention in the energy markets and explains why Congress has chosen to “pick winners and losers.” Part III examines the history of subsidies to both fossil fuels and renewable energy resources in light of those rationales and describes the divergent market trajectories of the two sets of subsidies. Part IV evaluates the subsidies on a qualitative basis, developing the thesis that the disparate market impacts derive from the differences in the way the subsidies are structured. This Part examines the subsidies’ relative risks, information costs, and transaction costs, liquidity and marketability. Part V examines the political economy associated with the subsidies, including their budgetary history, the first mover advantage available to fossil fuels, and the political advantages and administrative bias favoring subsidies that are shared with other sectors. It argues that certain structures have provided stability and certainty for fossil fuels and expanded their market share and that other structures have exposed renewables to legislative volatility and failure. Part VI discusses recent proposals for reform and Part VII concludes the article.